Implementation of website reservation system and online promotion for business development at Sejati Catering - Purwati, Nani; Sulistyo, Gunawan Budi; Kiswati, Sri; Hasan, Noor (Community Empowerment, 2025)
Sejati Catering faces obstacles in its manual promotion and order management system, hindering business development. This community service program aimed to enhance Sejati Catering's ability to leverage digital platforms for online promotion and reservations through website development. The program utilized a workshop methodology providing hands-on training in website management using a pre-built website. Evaluation results showed significant increases in knowledge of online promotion (100%), website management skills (90%), and promotional reach (80%). However, further copywriting training is recommended to optimize website content.